(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: Psychopathology in adolescents, seen as adaptation failure which involves deviations from age-appropriate behaviour, disrupting normal development and social functioning, especially in girls and require special attention. The aim of this study was to explore the correlation of psychopathology with personality traits, social skill and peer relation among adolescent girls. Methods: A cross-sectional study was done among 150 adolescent girls aged 16-19 years using purposive sampling technique from 17 colleges of Kamrup Metro, Assam, India. Personality traits, social skill, peer relation, and psychopathology were measured using the big five inventory, social skill scale, adolescent peer relation instrument, and adolescent psychopathology scale, respectively. Pearson correlation coefficients r ≥ 0.40 (moderate to strong) were reported irrespective of P value. Results: The results showed significant correlation between the neuroticism of personality traits (r=0.58). Neuroticism was found moderately correlated with six subdomains of the psychopathology distress scale, including academic problems (r=0.55), generalised anxiety disorder (r=0.57), post-traumatic stress (r=0.61), depression (r=0.55), eating disturbance (r=0.43), and interpersonal problems (r=0.57). A moderate positive correlation was found between the total score of the adolescent psychopathology distress scale and the peer relation scale (r=0.43). An inverse but weak correlation was found with psychopathology distress scale and social skills. Conclusion: Psychopathology distress of adolescent girls are correlated with neuroticism of personality traits, overall adolescent peer relation. However, an inverse but weak correlation was found with social skills.